Palmar pressure and perception of discomfort in the use of axillary crutches - Bonfim, Gabriel [UNESP]; Silva, Danilo [UNESP]; Neves, Erica [UNESP]; Plácido, João [UNESP]; Mantova, Ana [UNESP]; Medola, Fausto [UNESP]; Paschoarelli, Luís [UNESP] (Springer Nature, 2017)
The use of crutches is mainly related to healing processes after injuries or/and surgery of lower limbs. The design of the handle grips may influence the pressure distribution on the palm of the hand and it can influence the perception of discomfort. This study was aimed to verify whether different handle grip diameters influence the pressure distribution in the palm of the hand, as well as the perception of discomfort in the use of axillary crutches. It was used the Grip System Versatek (Tekscan Ink) and a Hand Map protocol to evaluate those variables. Results showed that each region of the palm of the hand was affected differently by each handle grip. There was no pattern for the distribution of pressure and the region with the highest number of occurrences of discomfort did not always attribute the highest degree of perceived discomfort by the subjects.
Keywords: Axillary crutches; Design; Discomfort; Ergonomics; Pressure mapping